Responses of regulatory and effector T-cells to low-dose interleukin-2 differ depending on the immune environment after allogeneic stem cell transplantation - Meguri, Yusuke; Asano, Takeru; Yoshioka, Takanori; Iwamoto, Miki; Ikegawa, Shuntaro; Sugiura, Hiroyuki; Kishi, Yuriko; Nakamura, Makoto; Sando, Yasuhisa; Kondo, Takumi; Sumii, Yuichi; Maeda, Yoshinobu; et al. (Frontiers in Immunology, 2022)
CD4+Foxp3+ regulatory T cells (Tregs) play a central role in the maintenance of immune tolerance after allogeneic hematopoietic stem cell transplantation (HSCT). Tregs promptly respond to low concentrations of IL-2 through the constitutive expression of high-affinity IL-2 receptors. It has been reported that low-dose IL-2 therapy increased circulating Tregs and improved clinical symptoms of chronic GVHD. Clinical studies of IL-2 therapy so far have mainly targeted patients in the chronic phase of transplantation when acute immune responses has subsided. However, the biological and clinical effects of exogenous IL-2 in an acute immune environment have not been well investigated. In the current study, we investigated the impact of exogenous IL-2 therapy on the post-transplant homeostasis of T cell subsets which influence the balance between GVHD and GVL in the acute phase, by setting the various immune environments early after HSCT in murine model. We initially found that 5,000 IU of IL-2 was enough to induce the active proliferation of Treg without influencing other conventional T cells (Tcons) when administered to normal mice. However, activated Tcons showed the response to the same dose of IL-2 in recipients after allogeneic HSCT. In a mild inflammatory environment within a threshold, exogenous IL-2 could effectively modulate Treg homeostasis with just limited influence to activated T cells, which resulted in an efficient GVHD suppression. In contrast, in a severely inflammatory environment, exogenous IL-2 enhanced activated T cells rather than Tregs, which resulted in the exacerbation of GVHD. Of interest, in an immune-tolerant state after transplant, exogenous IL-2 triggered effector T-cells to exert an anti-tumor effect with maintaining GVHD suppression. These data suggested that the responses of Tregs and effector T cells to exogenous IL-2 differ depending on the immune environment in the host, and the mutual balance of the response to IL-2 between T-cell subsets modulates GVHD and GVL after HSCT. Our findings may provide useful information in the optimization of IL-2 therapy, which may be personalized for each patient having different immune status.